Development Model at Children Correctional Institution in Improving Religious Living Awareness - Imam Asrofi; Dedi Mulyasana; Hendi S Muchtar (Ijtimā`iyya: Journal of Muslim Society Research, 2021)
Forms of education conducted by children correctional institution need to get a positive appreciation. However, evaluation should also be done consistently, so the correctional institution, as a place of education to prepare a human being ready to return to society, does not become a place to obtain new lesson to commit crimes. The purpose of this research is to find out education management; analyze problems and find out solutions and efforts to improve the implementation of coaching programs for children of correctional institution. The conclusion of this research is that Sukamiskin Children Correctional institution, Bandung, have done education through giving guidance to children of correctional facility to become better human beings, through both general and specific development programs through Open Junior High School (SMP) education. The problems found is the lack of feedback from correctional students in the learning process, the level of attendance of teachers, and the availability of supporting facilities and infrastructure. The solution offered are: (1) giving motivation for students of correctional facility to follow the development program that is done, especially in education; (2) cooperation with various parties; (3) motivation and support for all teachers to maintain the quality of learning; and (4) maximizing available facilities and infrastructures. The recommendations given for correctional students are expected to have a high awareness to change themselves from negative traits and behaviors as well as following the existing development program while in correctional facility. Moreover, correctional facilities are expected to improve the form of education services both from the elements of infrastructure and in its development programs that are carried out effectively, creatively, and efficiently. In addition, the community is expected to refrain from giving a negative judgment to ex-convicts, especially children of correctional facility, because they have received education while in doing their time.